2006
DOI: 10.1074/jbc.m505055200
|View full text |Cite
|
Sign up to set email alerts
|

Tyr-95 and Ile-172 in Transmembrane Segments 1 and 3 of Human Serotonin Transporters Interact to Establish High Affinity Recognition of Antidepressants

Abstract: In previous studies examining the structural determinants of antidepressant and substrate recognition by serotonin transporters (SERTs), we identified Tyr-95 in transmembrane segment 1 (TM1) of human SERT as a major determinant of binding for several antagonists, including racemic citalopram ((RS)-CIT). Here we described a separate site in hSERT TM3 (Ile-172) that impacts (RS)-CIT recognition when switched to the corresponding Drosophila SERT residue (I172M). The hSERT I172M mutant displays a marked loss of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
233
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(255 citation statements)
references
References 33 publications
20
233
0
2
Order By: Relevance
“…Nonetheless, the reduced SERT activity in the GK lines is still adequate for acute potentiation of 5-HT signaling by an SSRI (citalopram). One might expect that reduced SERT activity might have resulted in altered citalopram responsiveness; however, the dosage of citalopram optimized for responses in the TST paradigm may simply be above that required to distinguish SSRI sensitivities in vivo, although it should also be noted that the variants are not located in the predicted binding pocket for citalopram (26,27). We also found equivalent citalopram recognition by GK/ER variants in our transfection studies (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Nonetheless, the reduced SERT activity in the GK lines is still adequate for acute potentiation of 5-HT signaling by an SSRI (citalopram). One might expect that reduced SERT activity might have resulted in altered citalopram responsiveness; however, the dosage of citalopram optimized for responses in the TST paradigm may simply be above that required to distinguish SSRI sensitivities in vivo, although it should also be noted that the variants are not located in the predicted binding pocket for citalopram (26,27). We also found equivalent citalopram recognition by GK/ER variants in our transfection studies (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Previously, our heterologous expression studies demonstrated that the M172 substitution produces significant reductions in the potency of multiple SSRIs, cocaine, and cocaine analogues to inhibit 5-HT transport (28), despite the retention of normal potency of substrates (e.g., 5-HT, 3,4-methylenedioxymethamphetamine). Competition studies that used forebrain synaptosomes from M172 mice produced very similar results ( Fig.…”
Section: Synaptosomes Of Sert M172 Mice Display Reduced Sensitivity Tomentioning
confidence: 99%
“…By using the pharmacological differences displayed by human and Drosophila melanogaster SERTs (hSERT and dSERT), we identified variation at a single residue in TM3 (I172 in human and mouse, M167 in fly) proximal to the proposed binding site for 5-HT (28). Remarkably, when we substituted M172 for I172 in hSERT and mouse SERT (mSERT) cDNAs, we observed a significant, 100-to 1,000-fold reduction in potency of many SERT antagonists in transfected cells without an impact on basal 5-HT transport (28). Conversely, dSERT I167 displayed increased potencies for these same drugs.…”
mentioning
confidence: 99%
“…It has also been previously shown that the protonated amine of a series of sulfur-substituted -alkyl phenethylamines is essential for protein-ligand binding. Other commonly annotated significant binding residues include Ile172 and Tyr95, which allow for hydrophobic and aromatic interactions respectively 34 .…”
Section: Molecular Modellingmentioning
confidence: 99%
“…For this study the homology model of hSERT constructed by Jørgensen et al (2007) was used 33 . A number of previous studies have identified key binding residues involved in the binding of SERT ligands [33][34][35][36] . 5-HT, the natural substrate of SERT, and amphetamines such as 4-MTA interact with residues Ala96, Asp98 and Phe335 via binding of the protonated amine (Fig.…”
Section: Molecular Modellingmentioning
confidence: 99%